2015
DOI: 10.1371/journal.pone.0134732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Treatment Lactate Dehydrogenase Levels on Prognosis and Bevacizumab Efficacy in Patients with Metastatic Colorectal Cancer

Abstract: BackgroundTo investigate the impact of pre-treatment lactate dehydrogenase (LDH) levels on the outcome of patients with metastatic colorectal cancer treated with first-line chemotherapy with or without the anti-VEGF monoclonal antibody, bevacizumab, in a phase III prospective multicentre randomized ITACa (Italian Trial in Advanced Colorectal Cancer) trial.MethodsThree hundred and seventy patients enrolled onto the ITACa first-line trial were considered for this study, 176 receiving chemotherapy (either FOLFIRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…An inverse relationship between LDH levels and length of survival has also been identified in many tumor types, including melanoma 15, breast cancer 16, myeloma 17, hepatocellular carcinoma 18, seminoma 19, nasopharyngeal cancer 20, lung cancer 21, colorectal cancer 10, renal cancer 22, oral cancer 23, and pancreatic cancer 24. For gynecologic malignancies, a strong association between the elevated expression of LDH and an aggressive phenotype has been noted in patients with ovarian and uterine carcinoma 25, 26.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An inverse relationship between LDH levels and length of survival has also been identified in many tumor types, including melanoma 15, breast cancer 16, myeloma 17, hepatocellular carcinoma 18, seminoma 19, nasopharyngeal cancer 20, lung cancer 21, colorectal cancer 10, renal cancer 22, oral cancer 23, and pancreatic cancer 24. For gynecologic malignancies, a strong association between the elevated expression of LDH and an aggressive phenotype has been noted in patients with ovarian and uterine carcinoma 25, 26.…”
Section: Discussionmentioning
confidence: 95%
“…There is clear evidence that hypoxia can promote cancer development and it is involved in the resistance to treatment via the formation of new blood vessels 9. Lactate dehydrogenase (LDH) is known to be a marker of hypoxia, which plays an important role in the proliferation and metastasis of tumor cells 10. Moreover, pretreatment serum LDH levels have been found to correlate with the prognosis of patients with malignant diseases 11.…”
Section: Introductionmentioning
confidence: 99%
“…A higher level of LDH is significantly associated with poor survival in terminal cancer patients which confirmed by several studies. 39, 40. In bisphosphonate-treated breast cancer patients, an analysis demonstrated that LDH levels correlate with survival in patients with bone metastases 41.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Scartozzi et al suggested that mCRC patients treated with Bev and showing high pre-treatment LDH serum levels experienced an improved probability of response and an equivalent median PFS and OS when compared with patients with lower LDH serum levels [107]. Moreover, together with other research teams we demonstrated that mCRC patients with high LDH levels have a poor prognosis, and that the addition of Bev seems to improve prognosis of this group of patients, assimilating it to that of patients with low LDH levels [108, 109]. Similarly, Bar et al showed that high total serum LDH correlated with shorter PFS, and high hypoxia-related LDH isoenzymes correlated with worse PFS and OS, in patients treated with either cediranib or Bev [110].…”
Section: Monitoring Hypoxia During Antiangiogenic Treatments Could Hamentioning
confidence: 84%